2014
DOI: 10.1074/jbc.m114.573212
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Reversible Phosphorolysis and Hydrolysis Reactions of 2-O-α-Glucosylglycerol Phosphorylase

Abstract: Background: 2-O-␣-Glucosylglycerol phosphorylase (GGP) catalyzes the reversible phosphorolysis of glucosylglycerol and the hydrolysis of ␤-D-glucose 1-phosphate. Results: Crystal structures were determined for GGP complexed with glucose, isofagomine, and glycerol. Conclusion: A water-mediated hydrogen bond network that fixes glycerol is the key factor of the bifunctionality. Significance: The substrate recognition and reaction mechanisms of GGP were clarified in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This is the only activity identified in the subfamily, and starch synthase is the only phosphorylase known to generate oligosaccharide 1-phosphate. The activity and cloning of the gene encoding this enzyme were first Nihira et al 2014c Touhara et al 2014 reported for Corynebacterium in a patent (Igarashi et al 2005). The same activity of Mycobacterium tuberculosis was reported in a journal article with an explanation of the role of this enzyme (Elbein et al 2010).…”
Section: Gh13 Subfamilymentioning
confidence: 97%
See 1 more Smart Citation
“…This is the only activity identified in the subfamily, and starch synthase is the only phosphorylase known to generate oligosaccharide 1-phosphate. The activity and cloning of the gene encoding this enzyme were first Nihira et al 2014c Touhara et al 2014 reported for Corynebacterium in a patent (Igarashi et al 2005). The same activity of Mycobacterium tuberculosis was reported in a journal article with an explanation of the role of this enzyme (Elbein et al 2010).…”
Section: Gh13 Subfamilymentioning
confidence: 97%
“…This enzyme possesses moderate hydrolytic activity on βGlc1P and weak phosphate-dependent hydrolytic activity on kojibiose. Structural analysis of the enzyme revealed the mechanism of hydrolysis of a sugar 1-phosphate, a unique activity among phosphorylases (Touhara et al 2014). The strain also possesses two other unique GH 65 enzymes, branching oligosaccharide-forming maltose phosphorylase (Nihira et al 2012d) and potassium ion-dependent inverting trehalose phosphorylase (Nihira et al 2013a).…”
Section: Gh13 Subfamily 18mentioning
confidence: 98%
“…Only recently, has the first GG‐phosphorylase been identified and characterised from Bacillus selenitrireducens (Touhara et al . ).…”
Section: Heterosides In Other Organismsmentioning
confidence: 97%
“…Another GG synthesis reaction was described that reversibly phosphorylates GG to glucose-1-phosphate and glycerol, similar to the reversible reaction of sucrose phosphorylase. Only recently, has the first GG-phosphorylase been identified and characterised from Bacillus selenitrireducens (Touhara et al 2014).…”
Section: Heterosides In Other Organismsmentioning
confidence: 99%
“…2 B). The domain organization of LbMP is similar to other GH65 disaccharide phosphorylases, which include kojibiose phosphorylase from Caldicellulosiruptor saccharolyticus (CsKP) [ 37 ] and glucosylglycerol phosphorylase from Bacillus selenitireducens (BsGGP) [ 39 ]. Moreover, Paenibacillus sp.…”
Section: Enzyme Structure and Recognition Of The Substratementioning
confidence: 99%